Wrong Answers Only: Distractor Generation for Russian Reading Comprehension Questions Using a Translated Dataset - Никита Вячеславович Логин (Journal of Language and Education)
Background: Reading comprehension questions play an important role in language learning. Multiple-choice questions are a convenient form of reading comprehension assessment as they can be easily graded automatically. The availability of large reading comprehension datasets makes it possible to also automatically produce these items, reducing the cost of development of test question banks, by fine-tuning language models on them. While English reading comprehension datasets are common, this is not true for other languages, including Russian. A subtask of distractor generation poses a difficulty, as it requires producing multiple incorrect items.